The economic implications of peace in Ireland - Casey, Michael (Statistical and Social Inquiry Society of Ireland, 1995)
This symposium is concerned with the possible effects of peace between the two parts of Ireland on the economies of both and on the island of Ireland as a whole. It goes without saying that the greatest and overwhelming dividend of peace is the ending of loss of life and human misery, especially in NI. The question before us tonight is the secondary one of whether there is likely to be an economic bonus flowing from the peace and what form it might take. Any attempt to answer this question must be speculative at best - for a number of reasons. First, there are no analogues in recent history to guide us. The ending of the Cold War and the Re-unification of Germany, for example, could hardly be taken as even approximate models. Second, the results of any "positive shock" are difficult to predict and, in this instance the difficulties are compounded by attitudinal factors, weak economic links and by data deficiencies.
Symposium on the economic implications of peace in Ireland
Read before the Society, 23 February 1995
Keywords: Peace process; Economic growth; 314.15